2000
DOI: 10.1093/jat/24.4.305
|View full text |Cite
|
Sign up to set email alerts
|

A Fatality Due To Injection of Tiletamine and Zolazepam*

Abstract: A 22-year-old male with more than 28 needle marks on his right arm was found dead. First, he was suspected as a drug abuser. Blood, urine, spleen, and injection-site tissue was collected during autopsy. The blood and urine specimens were screened for drugs. Immunoassay studies did not show any illegal drugs. However, two unidentified peaks were isolated in both of these biological fluids by routine gas chromatography-flame-ionization detection (GC-FID) and thermionic specific detection. Additional gas chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…However, the details of extraction methodology and validation parameters were unclear from their report. Two methods employing GC/MS instrumentation have also been reported [10,11]. Chung et al [10] extracted tiletamine and zolazepam from 1 ml of alkalinized blood with 5 ml of ethyl acetate three times, back-extracted the pooled ethyl acetate into acid, and reextracted the acidic solution twice with 5 ml of ethyl acetate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the details of extraction methodology and validation parameters were unclear from their report. Two methods employing GC/MS instrumentation have also been reported [10,11]. Chung et al [10] extracted tiletamine and zolazepam from 1 ml of alkalinized blood with 5 ml of ethyl acetate three times, back-extracted the pooled ethyl acetate into acid, and reextracted the acidic solution twice with 5 ml of ethyl acetate.…”
Section: Resultsmentioning
confidence: 99%
“…Two methods employing GC/MS instrumentation have also been reported [10,11]. Chung et al [10] extracted tiletamine and zolazepam from 1 ml of alkalinized blood with 5 ml of ethyl acetate three times, back-extracted the pooled ethyl acetate into acid, and reextracted the acidic solution twice with 5 ml of ethyl acetate. This publication was a case report on a death related to abuse of Telazol ® and the authors did not perform a formal validation of the assay procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These anesthetics are not only traded on the illicit market under different names, but are also openly sold without restrictions to the public in some drugstores. Current conditions could be the cause of the resulting misuse and abuse of veterinary anesthetics, as well as possible socio-economic losses [3]. The main goals of the survey were to determine the actual state of animal anesthetic drug use, and to inform the public on survey responses from veterinarians and researchers in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Abuse or misuse of Zoletil®, a veterinary anesthetic combination (1:1) of the N-methyl-D-aspartate (NDMA) receptor antagonist, tiletamine, and the benzodiazepine, zolazepam, has been reported in several studies (Chung et al, 2000;Cording et al, 1999;Kim, 2011;Lee et al, 2009;Quail et al, 2001;Redmond and Herman, 2002). In previous studies, we have demonstrated that this combination is rewarding and reinforcing in rats, but these effects were only manifested in animals repeatedly preexposed to Zoletil® or to other pharmacologically-related psychoactive drugs.…”
Section: Introductionmentioning
confidence: 99%